Efektivitas Peran Penyuluh Pertanian dan Produktivitas Kerja Petani pada Usahatani Padi Sawah di Desa Ambuulanu Kecamatan Pondidaha Kabupaten Konawe - Oktafiani Oktafiani; Dasmin Sidu; Salahuddin Salahuddin (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2021)
This research aimed to: (1) Analyzed the role taken by agriculture instructor in Ambuulanu, District of Pondidaha, Konawe Regency. (2) Analyzed productivity of farmer work on the rice farming rice field in Ambuulanu, District of Pondidaha, Konawe Regency. (3) Analyzed  the effectiveness of the role of agriculture instructor in Ambuulanu, District of Pondidaha, Konawe Regency. (4) Analyzed relation of the role effectiveness between agriculture instructor and productivity of farmer work on the rice farming rice field in Ambuulanu, District of Pondidaha, Konawe Regency. This research was carried out in  Ambuulanu, District of Pondidaha, Konawe Regency on September 2020 with 46 respondents which taken by simple random sampling. The data is analyzed by descriptive and analysis correlation of rank spearman. The result of this research showed that the role of agriculture instructor in Ambuulanu categorized as good. Work productivity of the rice field farmer in Ambuulanu categorized as very good. The role of agriculture instructure in Ambuulanu categorized as effective. The effectiveness of agriculture instructure role has significant relation with work productivity of farmer of rice field.